Soil genesis in a marine terrace sequence of Sicily, Italy - Stephen Wagner; Edoardo A.C. Costantini; Daniela Sauer; Karl Stahr (Revista Mexicana de Ciencias Geológicas)
Knowledge about the rates of pedogenic processes is essential to understand landscape development and history. It can be attained by the quantitative investigation of soil chronosequences. In this work, the development of Chromic Luvisols in the Mediterranean is addressed. The soils investigated are located on five uplifted Pleistocene marine terraces in south-western Sicily, and have developed on calcareous marine and fluvial sediments. The soil on the highest terrace is a Ferri-Profondic Luvisol, while soils on the lower terraces represent a Chromi-Profondic Luvisol (Bathifragic), a Chromi-Profondic Luvisol and two Bathicalci-Chromic Luvisols. The soils on the 1st (lowest) and 2nd terrace are 100 cm thick, the one on the 3rd terrace, 160 cm and those on the 4th and 6th (highest) terrace more than 200 cm. All soils are decalcified, while greater CaCO3 contents in the Ap horizons of the soils on the three lower terraces are due to deposition of younger calcareous fluvial sediments. Soil pH (water) drops from pH 7.7–8.9 in the soils on the three lower terraces to values below pH 7 in the soils on the two higher terraces. In general, the chemical alteration and the leaching of silicic acid increase with elevation, and are most pronounced on the 4th and 6th terrace. Clay illuviation and associated translocation of Fe, Al and K is pronounced in all soils. The clay minerals include kaolinite, illite and expandable three-layer silicates. Irregularly interstratified clay minerals are composed of illite, vermiculite, smectite and chlorite, and usually constitute 20–40 % of all clay minerals, indicating proceeding soil development. The comparatively more advanced weathering and the high kaolinite content on the most elevated terrace point to soil development under warmer and wetter climate, that is early Pleistocene or earlier. The soil on the 4th terrace is more developed than the soils on the less elevated terraces.